Subtle Influence of ACE2 Glycan Processing on SARS-CoV-2 Recognition - Allen, Joel D. (J Mol Biol, 2021)
The severity of SARS-CoV-2 infection is highly variable and yet the molecular basis for this effect remains elusive. One potential contribution are differences in the glycosylation of target human cells, particularly as SARS-CoV-2 has the capacity to bind sialic acid which is a common, and highly variable, terminal modification of glycans. The viral spike glycoprotein (S) of SARS-CoV-2 and the human cellular receptor, angiotensin-converting enzyme 2 (ACE2) are both densely glycosylated. We therefore sought to investigate whether the glycosylation state of ACE2 impacts the interaction with SARS-CoV-2 viral spike. We generated a panel of engineered ACE2 glycoforms which were analyzed by mass spectrometry to reveal the site-specific glycan modifications. We then probed the impact of ACE2 glycosylation on S binding and revealed a subtle sensitivity with hypersialylated or oligomannose-type glycans slightly impeding the interaction. In contrast, deglycosylation of ACE2 did not influence SARS-CoV-2 binding. Overall, ACE2 glycosylation does not significantly influence viral spike binding. We suggest that any role of glycosylation in the pathobiology of SARS-CoV-2 will lie beyond its immediate impact of receptor glycosylation on virus binding.